Perbandingan Absolute Lymphocyte Count (ALC) Antara Pasien Terkonfirmasi Dengan Probable Covid 19 Di RSUD Pesawaran - Denny Andika Kurniawan; Winda Trijayanthi Utama (Medula, 2026)
Coronavirus Disease 2019 (COVID-19) is a broad group of viruses known to cause diseases with a diverse clinical spectrum, ranging from mild symptoms to severe disorders in humans. These viruses are zoonotic, meaning they can be transmitted from animals to humans, posing a major challenge in infection control efforts. In addition, variations in immune responses in each individual cause the clinical picture of Covid-19 to vary greatly, including changes in laboratory parameters such as absolute lymphocyte count (ALC). This study was conducted to analyze the differences in ALC values in patients with a confirmed diagnosis of Covid-19 compared to patients categorized as probable Covid-19 at the Pesawaran Regional General Hospital. The study design used an observational analytical method with a cross-sectional approach. Data processing and analysis were performed using an independent t-test to assess the difference in means between the two groups. The total sample consisted of 45 patients, namely 20 patients with confirmed Covid-19 and 25 patients with probable Covid-19. The results showed that the mean ALC value in the confirmed group was 1,241.5/µL, while in the probable group it reached 1,812.59/µL. These findings indicate a statistically significant difference between the mean ALC of the two groups, with a p-value of 0.0001. This difference also supports the findings of previous studies that lymphopenia is more commonly found in patients with verified Covid-19 infection. Thus, this study confirms that Covid-19 confirmation status is associated with changes in ALC, which can be a supporting clinical parameter in the evaluation and monitoring of patient conditions.